Desenvolvimento de sistemas estabilizados por tensoativos para a administração tópica de lapachol no tratamento de leishmaniose - Alves, Suely Moraes (2022)
Leishmaniasis is a neglected infectious disease, caused by more than 20 species of Leishmania and which manifests itself in two main forms, tegumentary (cutaneous or mucocutaneous) or visceral. The treatment of this disease requires long duration, high cost and can have several adverse effects. An alternative would be the use of natural compounds, such as lapachol, which has leishmanicidal activity and interesting characteristics for topical application. Thus, this study aimed to develop and characterize formulations from systems stabilized by surfactants containing lapachol to evaluate the leishmanicidal activity against Leishmania spp promastigotes. The formulations were prepared using the phase diagram, using distilled water, Citrus sinensis essential oil as the oil phase, and Tween 20:Eumulgin Co 40, as surfactant and co-surfactant, respectively, which were combined in a 1:1 ratio. and 2:1. Then, two formulations obtained from the diagram that presented the largest area of formation of nanostructured systems (ratio 2:1) were selected: O5TC25A70 (transparent liquid system) and O5TC45A50 (transparent viscous system). Lapachol was incorporated into the formulations and the structural characterization of the systems was performed by means of polarized light microscopy (MLP), rheological and low angle X-ray scattering (SAXS) analyses. Then, the formulations were submitted to in vitro skin permeation assays, evaluation of cytotoxicity in RAW macrophages and determination of leishmanicidal activity on promastigote forms of Leishmania braziliensis, Leishmania amazonensis and Leishmania major species. As a result, the formulations showed isotropy and Newtonian behavior, characteristic of microemulsions. The SAXS results confirmed the formation of microemulsions. The formulations showed a permeation-promoting effect on the skin, mainly the formulation O5TC25A70, capable of increasing four times the permeated amount of lapachol in the skin after 24h of the experiment compared to the control. In the biological assays, low cytotoxicity in macrophages and leishmanicidal activity from 100 to 383 µg.mL -1 were observed for the formulations. In addition, an improvement in the activity of lapachol was observed with the essential oil of C. sinensis in the formulation O5TC45A50L. Thus, the microemulsions obtained may therefore represent promising vehicles for topical administration and treatment of cutaneous leishmaniasis.